ORIGINAL COST AND PUBLIC UTILITY REGULATION. - Dein, Raymond C. (The Accounting Review, 1949)
The systems of accounts for public utilities have been revised more or less extensively since 1937. Of the several interesting features embodied in these systems, one particular innovation, the original cost procedure, really deserves more careful attention than accountants have seemed willing to give it. The principal advocate (but not the originator of the idea) of the original cost procedure for utility systems of accounts has been the Committee on Statistics and Accounts of the National Association of Railroad and Utility Commissioners (NARUC). The original cost procedure ingeniously utilizes accounting techniques to isolate and emphasize information which the regulatory authorities have said they must have in order to discharge their regulatory functions adequately. Depreciation is universally prescribed for public utilities in modern uniform systems of accounts. This requirement raises the interesting question of whether the acquisition adjustment account is to be subjected to similar periodic write-off. The system, in fact, does provide that the amounts recorded in this account with respect to each property acquisition shall be depreciated, amortized, or otherwise disposed of, as the Commission may approve or direct.